ASC annual report 2006/2007 (Annual report Australian Sports Commission, 2007)
One of the key roles of the ASC is to provide leadership to the Australian sports system in the area of planning for the future. Australian sport is facing a number of challenges and opportunities in the lead-up to the Beijing 2008 Olympics and beyond. Australia's sporting dominance is under direct challenge on a number of fronts, including increased funding of elite sport in our competitor countries, better funding and targeting of niche sports by our competitors, the emergence of countries such as China and India, and Australia's naturally small talent pool. This increasingly competitive international environment makes it vital for Australia to 'sharpen' its edge in quality coaching, sports science, sports medicine and other support services, including state-of-the-art training and testing facilities.